Patient with Transverse Myelitis and Physiotherapy Management: A Case Study - Hossain, Md. Emran; Dey, Ganesh; Munna, Nazmun Nahar; Hossain, Saddam; Rahman, Zakia; Tasmim, Tamanna; Hossain, Md. Saiyed; Rahman, Md. Atiar; Islam, Asma (Archives of Clinical and Medical Case Reports, 2024)
Background: Transverse myelitis (TM) is a neurological disorder characterized by inflammation of the spinal cord, resulting in sensory, motor, and autonomic dysfunction. Individuals with TM often experience challenges with dynamic sitting balance, impacting their functional independence and quality of life. While no definitive cure exists for TM, evidence-based physiotherapy interventions have been shown to improve functional outcomes and enhance overall well-being. Objectives: This case-based study aims to describe the evidence-based physiotherapy management for a patient diagnosed with transverse myelitis, focusing on interventions aimed at improving dynamic sitting balance. Intervention: The physiotherapy intervention consisted of a tailored program designed to address the specific impairments and functional limitations associated with TM. Key components included exercises targeting lower limb strength and flexibility, core stabilization, balance training, gait retraining, and education on assistive devices. Functional task-oriented training was also emphasized, with a focus on activities aimed at enhancing dynamic sitting balance. Outcomes: Following a four-week intervention comprising twelve 30-minute sessions, the patient demonstrated notable improvements in mobility and balance. Specifically, the patient exhibited enhanced dynamic sitting balance, reflected in improved performance on functional tasks. Conclusion: This evidence-based physiotherapy program highlights the potential for improving dynamic sitting balance and overall functional capacity in individuals with transverse myelitis. Regular participation in targeted interventions may help mitigate the impact of TM on daily activities and enhance quality of life.